Pharmacologic interrogation of patients with esophagogastric junction outflow obstruction using amyl nitrite. Issue 9 (25th June 2019) - Babaei, Arash; Shad, Sadaf; Szabo, Aniko; Massey, Benson T.
Abstract: Background: The Chicago Classification of esophageal motility includes a group of patients who show evidence of esophagogastric junction outflow obstruction (EGJOO) as demonstrated by elevated integrated relaxation pressure (IRP) and preserved peristalsis. Our aim is to classify EGJOO patients based on response to amyl nitrite (AN) during high‐resolution manometry. Methods: Patients were considered to have true EGJOO if elevated IRP during supine swallow persisted in the upright position and was associated with high intrabolus pressure. The EGJ response to AN was compared between patients with achalasia type 2 (A2) and normal esophageal motility. Based on the relaxation gain (deglutitive IRP—AN IRP) value that best discriminated these two groups (10 mm Hg), patients with true EGJOO were categorized as being in either the AN‐responsive (AN‐R) or AN‐unresponsive (AN‐U) subgroups. Key Results: In the group of 49 patients with true EGJOO, the AN response classified 27 patients (IRP = 25 ± 10 mm Hg) with AN‐R and 22 patients (IRP = 20 ± 5 mm Hg) with AN‐U ( P = 0.2). In AN‐R, AN produced a relaxation gain and rebound after‐contraction response at the EGJ comparable to A2 patients. AN‐U patients had an elevated IRP after AN and a relaxation gain similar to normal esophageal motility patients. AN‐U patients were obese and had higher prevalence of sleep apnea ( P < 0.05). Conclusions: Among patients with true EGJOO, only half have pharmacologic evidence of impaired LES relaxation. Pharmacologic interrogation of the EGJ is thus necessary to identify the subgroup of EGJOO patients who could be expected to benefit from LES ablative therapies. Abstract : EGJOO may be reported in 3%‐17% of patients who undergo esophageal manometry, but in two‐thirds of EGJOO patients, the elevated IRP is not associated with true outflow obstruction to the bolus flow (as evidenced by normal IRP in the upright position and/or normal intrabolus pressure). Among the remainder of patients with true EGJOO and not on chronic daily opioids, only half have a pharmacologic response to inhaled amyl nitrite (AN) suggestive of an early form of achalasia.